PERNIKAHAN TIDAK TERCATAT DI KECAMATAN BUNGUS TELUK KABUNG - Harry Pribadi Garfes (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2019)
This research is motivated by many unregistered marriages in Bungus Teluk Kabung Sub-district which was proven by the KUA who found a fake marriage book every month and those who committed marriages were not recorded. The subject matter is: what factors cause the occurrence of marriages are not recorded in Bungus Teluk Kabung Sub-district, what efforts have been made by KUA and public figure in minimizing marriages are not recorded, what are the obstacles faced by the parties KUA and public figures in minimizing marriages are not recorded. The type of this research is field research used a qualitative approach, while the type of data is primary data by conducting interviews with KUA and public figure, and the secondary data are theoretical book related to these discussion. Data analysis in this research was carried out by descriptive analysis. The underlying factors of unregistered marriage are: marriage by accident, polygamy, not approved by parents to marry, lack of public legal awareness about marriage registration, weak economy, lack of socialization from KUA. The efforts that have been done that is; inputting every event of marriage to Simkah, directing marriage of itsbât for unregistered marriages, conveying the importance of marriage registration through lectures. Therefore, constraints faced namely; there is no strict legal regulation, unrecorded marriages are carried out clandestinely, those who are married cannot be advised, and there are many immigrants from outside the area.